2019
DOI: 10.21272/mmi.2019.2-25
|View full text |Cite
|
Sign up to set email alerts
|

Paradox of nepotism in enterprises in Poland and Ukraine: social capital perspective

Abstract: The aim of the article is to analyse the phenomenon of nepotism, its effects in small and medium enterprises in Poland and Ukraine and their negative impact on social capital. Systematization literary sources and approaches for solving the problem of nepotism indicate that it is quite a common phenomenon in central and east European countries. Nepotism caused a lot of negative impact on organizations. It means, that in the organization, where nepotism is common employees have less motivation, job satisfaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Cronyism was assessed negatively, more severely than nepotism, which is consistent with previous studies of this phenomenon (Sroka and Vveinhardt 2018;Onoshchenko and Williams 2014;Williams and Onoshchenko 2014;Padgett and Morris 2005;Padgett et al 2015;Abdalla et al 1998;Ignatowski et al 2019), however, the change in the respondents' opinions on the assessment of cronyism, as in the case of nepotism, was insignificant. In addition, in the interviews with business owners, no arguments were made about a stricter assessment of cronyism during the pandemic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cronyism was assessed negatively, more severely than nepotism, which is consistent with previous studies of this phenomenon (Sroka and Vveinhardt 2018;Onoshchenko and Williams 2014;Williams and Onoshchenko 2014;Padgett and Morris 2005;Padgett et al 2015;Abdalla et al 1998;Ignatowski et al 2019), however, the change in the respondents' opinions on the assessment of cronyism, as in the case of nepotism, was insignificant. In addition, in the interviews with business owners, no arguments were made about a stricter assessment of cronyism during the pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Comparison of nepotism depending on membership in the public and private sector, age and gender, as well as Poland and Lithuania (Sroka and Vveinhardt 2020;Vveinhardt and Sroka 2020). The understanding of nepotism from the perspective of family businesses was also undertaken (Ignatowski et al 2019). Al-Youbi et al (2020) dealt with the issue of acceptance for organizational nepotism from the perspective of belonging to the Protestant and Catholic denominations.…”
Section: Introductionmentioning
confidence: 99%
“…While both states share the same past of the socialist market, the level of their autonomy differed similarly to that between Poland and Ukraine, which was more integrated in the Soviet Union. The study conducted in the context of the latter countries showed significant differences in preferences with regard to nepotism too [79].…”
Section: Hypothesis 3 (H3)mentioning
confidence: 88%
“…However, to the authors' knowledge, until now, the connection between organisational climate, nepotism, and favouritism has only been researched according to separate variables, which highlighted the need for a systematic perspective. Research shows that nepotism and favouritism is a rather frequent phenomenon in postcommunist countries of Central and Eastern Europe (e.g., Onoshchenko and Williams, 2014;Ignatowski et al, 2019); for this reason, research was conducted by surveying persons who work in organisations of Lithuania.…”
Section: Samplementioning
confidence: 99%